2010
DOI: 10.1186/1471-2407-10-642
|View full text |Cite
|
Sign up to set email alerts
|

The use of chemotherapy regimens carrying a moderate or high risk of febrile neutropenia and the corresponding management of febrile neutropenia: an expert survey in breast cancer and non-Hodgkin's lymphoma

Abstract: BackgroundThe use of chemotherapy regimens with moderate or high risk of febrile neutropenia (defined as having a FN incidence of 10% or more) and the respective incidence and clinical management of FN in breast cancer and NHL has not been studied in Belgium. The existence of a medical need for G-CSF primary and secondary prophylaxis with these regimens was investigated in a real-life setting.MethodsNine oncologists and six hematologists from different Belgian general hospitals and university centers were surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 23 publications
0
18
1
Order By: Relevance
“…Interestingly, the reported incidence of fn associated with specific chemotherapy regimens is higher in clinical practice than in clinical trials 19,21,[23][24][25] . Likewise, although international guidelines are clear on the use of g-csf prophylaxis, data on such use in clinical practice remain scarce.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Interestingly, the reported incidence of fn associated with specific chemotherapy regimens is higher in clinical practice than in clinical trials 19,21,[23][24][25] . Likewise, although international guidelines are clear on the use of g-csf prophylaxis, data on such use in clinical practice remain scarce.…”
Section: Resultsmentioning
confidence: 97%
“…Although the risk of fn for several chemotherapy regimens has been widely described within the context of clinical trials, only a few studies have described the occurrence of fn in clinical practice [19][20][21][22][23] . Interestingly, the reported incidence of fn associated with specific chemotherapy regimens is higher in clinical practice than in clinical trials 19,21,[23][24][25] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a study by Gerlier et al 26 reported a fn event for 31% of breast cancer patients who did not receive g-csf primary prophylaxis, and another recent study (Rajan et al 27 ) reported that primary prophylaxis with a g-csf led to a 16% reduction in hospitalizations within the first 3 months of chemotherapy initiation.…”
Section: Figure 1 Reasons For Administration Of Filgrastim (Fil) or Pmentioning
confidence: 99%
“…Expert surveys are useful as alternative methods to obtain information when objective clinical and epidemiological data are incomplete [19,41,42]. Expert surveys are useful as alternative methods to obtain information when objective clinical and epidemiological data are incomplete [19,41,42].…”
Section: Limitationsmentioning
confidence: 99%